Performance of Cellulose and Gum-based Oleogelators to Form Oleogels in Different Oil Systems - Trirahayu, Dhyna Analyes; Abidin, Akhmad Zainal; Putra, Ridwan P.; Hidayat, Achmad Syarif; Perdana, Muhammad Iqbal (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
One of the formed fats that is attracting attention as an alternative to trans-fat is oleogel. Oleogels can be formed using edible and non-edible vegetable oils, depending on the desired application. In this study, we used an emulsion-template approach with three oil systems: canola oil, sunflower oil, and castor oil, and combined hydroxypropyl methylcellulose (HPMC) and xanthan gum (XG) as oleogelators in specific ratios to form oleogel. Stable oleogels were formed when both oleogelators were present in the system. The oil binding capacity of the oleogel with respect to the amount of oil loss varied from less than 5% to more than 30%, depending on oil saturated fatty acid composition and HPMC:XG ratio. Higher saturated fatty acid concentration in the oil strengthens the oleogel matrix and reduces the oil loss rate. High HPMC composition and low XG composition reduce the oil binding ability of oleogels. In oleogel systems, HPMC acts as an emulsifier and XG acts as a thickener, resulting in a lower-than-average XG concentration and a thinner gel. Although the structure and color of oleogels are very stable over 28 days of storage, the rate of oxidation still needs to be minimized. Heating the oleogel system and the presence of aqueous phase can accelerate the oxidation of the oleogel, which can shorten its shelf-life and limit its applications, especially in the food industry.